2020
DOI: 10.14742/ajet.4653
|View full text |Cite
|
Sign up to set email alerts
|

Do academics and university administrators really know better? The ethics of positioning student perspectives in learning analytics

Abstract: Increasingly learning analytics (LA) has begun utilising staff- and student-facing dashboards capturing visualisations to present data to support student success and improve learning and teaching. The use of LA is complex, multifaceted and raises many issues for consideration, including ethical and legal challenges, competing stakeholder views and implementation decisions. It is widely acknowledged that LA development requires input from various stakeholders. This conceptual article explores the LA literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…This is not a new challenge but instead a continuous issue experienced in design practice in general (Sanders & Stappers, 2008). In academia, both the CSCL and the learning analytics communities are calling for greater learner/educator agency (Prinsloo & Slade, 2016;Tchounikine, 2019), and the lack of students' voice in the development of learning analytics is being questioned (West, Luzeckyj, Toohey, Vanderlelie, & Searle, 2020). Yet, even if teachers and students are invited to be part of a learning analytics project as partners, further challenges can emerge in integrating potentially divergent stakeholder views or conflicts between theory and teachers' pedagogical beliefs.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…This is not a new challenge but instead a continuous issue experienced in design practice in general (Sanders & Stappers, 2008). In academia, both the CSCL and the learning analytics communities are calling for greater learner/educator agency (Prinsloo & Slade, 2016;Tchounikine, 2019), and the lack of students' voice in the development of learning analytics is being questioned (West, Luzeckyj, Toohey, Vanderlelie, & Searle, 2020). Yet, even if teachers and students are invited to be part of a learning analytics project as partners, further challenges can emerge in integrating potentially divergent stakeholder views or conflicts between theory and teachers' pedagogical beliefs.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…Kitto, Lupton, Davis, and Waters (2017) suggested that despite a narrative that positions LA as a field aiming to enhance student learning, few student-facing solutions have emerged beyond the often-dominant narratives of 'at risk' and 'retention'. West et al (2020) concurred that much of the literature reflects an academic, teacher-centric or institutional view. In their exploration of the LA literature related to student perceptions on the development and use of LA, the authors found that student perspectives were largely absent from LA development and application.…”
Section: Learning Analytics Research Published In Ajetmentioning
confidence: 98%
“…They also found that student-facing dashboards (displays that visualise or present information in a way that allows the end user to quickly make sense of data at a glance) were largely developed from the view of the academic or institution and based on what those academics or institutions thought would be useful for students rather than from a student perspective. While research in the area of student perspectives in LA is growing, West et al (2020) argue that a lack of input from students raises serious ethical concerns and suggests a need for several actions, including, most prominently, engaging students.…”
Section: Learning Analytics Research Published In Ajetmentioning
confidence: 99%
See 1 more Smart Citation
“…Without clarification of these questions, a fear of data misuse and the development of new but possibly unwanted power relationships remains. It seems pertinent that students have a say in these regulations (West et al 2020).…”
Section: Impact Of La On Privacy and Data Protectionmentioning
confidence: 99%